Role of methyl jasmonate in the expression of mycorrhizal induced resistance against Fusarium oxysporum in tomato plants - Nair, Aswathy; Kolet, Swati P.; Thulasiram, Hirekodathakallu V.; Bhargava, Sujata (Physiological and Molecular Plant Pathology, 2015)
Arbuscular mycorrhiza (AM) colonization led to a decrease in the severity of fusarium wilt disease caused by Fusarium oxysporum f. sp. lycopersici in tomato plants. The involvement of two plant defense hormones, namely methyl jasmonate (MeJA) and salicylic acid (SA), in the expression of mycorrhiza induced resistance (MIR) against this vascular pathogen was studied in the AM colonized and non-colonized (controls) plants. Activity of lipoxygenase (LOX), which plays a role in jasmonic acid (JA) biosynthesis, as well as levels of methyl jasmonate (MeJA) increased in AM colonized plants as compared to controls, but did not show any further changes in response to F. oxysporum inoculation. On the other hand, activity of phenylalanine ammonia lyase (PAL), which is an enzyme from salicylic acid (SA) biosynthetic pathway, as well as SA levels, increased in both controls and AM colonized plants in response to application of F. oxysporum spores. Hence the JA and not the SA signalling pathway appeared to play a role in the expression of MIR against this vascular pathogen. The resistance observed in AM colonized plants was completely compromised when plants were treated with the JA biosynthesis inhibitor salicylhydroxamic acid (SHAM). This confirmed that the AM-induced increase in JA levels was involved in the expression of resistance toward F. oxysporum. The SA response gene pathogenesis-related 1 (PR1) showed an increased expression in response to F. oxysporum infection in SHAM treated AM colonized plants as compared to plants that were not treated with this JA inhibitor. This suggested the possibility that JA inhibited SA responses, at least in the roots. AM colonization therefore appeared to prime plants for improved tolerance against the vascular pathogen F. oxysporum, which was mediated through the JA signalling pathway. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Fusarium wilt; Glomus fasciculatum; Methyl jasmonate; Mycorrhiza induced resistance; Salicylic acid; Tomato

Systemic jasmonic acid modulation in mycorrhizal tomato plants and its role in induced resistance against alternaria alternata - Nair, A.; Kolet, Swati P.; Thulasiram, H. V.; Bhargava, S. (Plant Biology, 2015)
Tomato plants colonised with the arbuscular mycorrhizal (AM) fungus Glomus fasciculatum show systemic induced resistance to the foliar pathogen Alternaria alternata, as observed in interactions of other AM-colonised plants with a range of pathogens. The role of jasmonic (JA) and salicylic (SA) acid in expression of this mycorrhiza-induced resistance (MIR) against A.alternata was studied by measuring: (i) activity of enzymes reported to be involved in their biosynthesis, namely lipoxygenase (LOX) and phenylammonia lyase (PAL); and (ii) levels of methyl jasmonate (MeJA) and SA. Transcript abundance of some defence genes associated with JA and SA response pathways were also studied. Both LOX and PAL activity increased twofold in response to pathogen application to control plants. AM-colonised plants had three-fold higher LOX activity compared to control plants, but unlike controls, this did not increase further in response to pathogen application. Higher LOX activity in AM-colonised plants correlated with four-fold higher MeJA in leaves of AM-colonised plants compared to controls. Treatment of plants with the JA biosynthesis inhibitor salicylhydroxamic acid (SHAM) led to 50% lower MeJA in both control and AM-colonised plants and correlated with increased susceptibility to A.alternata, suggesting a causal role for JA in expression of MIR against the pathogen. Genes involved in JA biosynthesis (OPR3) and response (COI1) showed six- and 42-fold higher expression, respectively, in leaves of AM-colonised plants compared to controls. AM-colonised plants also showed increased expression of the SA response gene PR1 and that of the wound-inducible polypeptide prosystemin. Our results suggest that the systemic increase in JA in response to AM colonisation plays a key role in expression of MIR against A. alternata.
Keywords: Alternaria alternata; AM colonisation; induced resistance; Methyl jasmonate; salicylhydroxamic acid; Salicylic acid; Solanum lycopersicum